Vitamin A supplemementation and adverse events risk assessment and resources - United Nations Children's Fund (Geneva : UNICEF)
This CD-ROM is a risk assessment and learning tool developed for use by all those involved in the implementation of Vitamin A supplementati on.
Based on a report entitled "The potential for rumors and adverse eve nts associated with micronutrient programs: recommendations for prevent ion, preparation, and response" prepared by the USAID/CHANGE project.
System requirements: Adobe Acrobat Professional
Keywords: Vitamin A deficiency -- Prevention & control